Benefits of Aloe vera in dentistry - S P Mangaiyarkarasi; T Manigandan; M Elumalai; Priyanka K Cholan; Roopam Pal Kaur (Wolters Kluwer Medknow Publications, 2015)
Aloe vera (Aloe barbadensis) is a plant that belongs to Liliaceae family. The name Aloe derives from the Arabic word "Alloeh" meaning shining bitter substance while "vera" in Latin means true. It contains various minerals and vitamins. It has got various properties such as immunomodulatory, antiviral and antiinflammatory in nature. A. vera can play a significant role in dentistry in treatment of lichen planus, oral submucous fibrosis, recurrent aphthous stomatitis, alveolar osteitis, periodontitis, etc.